Comparing the Effectiveness of Self-determination Skills Training and Affect Phobia Therapy on the Meta-Emotional and Mental Toughness in Adolescent Girls with Sexual Abuse Experience - Fatemeh Dafeian; Zahra Yousefi (روانشناسی بالینی و شخصیت)
Introduction: The sexual abuse of children and adolescents is a significant public health issue that leads to a variety of detrimental social, cultural, and familial consequences. The aim of the present study was to compare the effectiveness of self-determination skills training and agoraphobia treatment on emotional regulation and psychological resilience in adolescent girls who have experienced sexual abuse.Method: This study employed a quasi-experimental design featuring a pretest-posttest approach, including a control group and a two-month follow-up period. The statistical population comprised all adolescent girls who experienced sexual abuse in Isfahan in 2023. 45 participants were selected using convenience sampling and subsequently randomly assigned to three groups. The data collection tools used in this study were the Mittmannsgruber Hyperemotion Questionnaire (2009) and the Kloof et al. Psychological Resilience Questionnaire (2002). The first experimental group underwent ten sessions of self-determination skills training based on the Field and Hoffman protocol (1994), while the second experimental group participated in eight sessions of agoraphobia treatment following the McCullough protocol (2003). The control group was also placed on a waiting list. The data were analyzed using SPSS version 23, employing a mixed analysis of variance with repeated measures statistical method.Results: The results indicated that the mean ages of the participants in the self-determination skills training group, the agoraphobia group, and the control group were 15.2, 16.5, and 15.7 years, respectively. Furthermore, the members of all three groups were comparable and homogeneous. The findings indicated that both self-determination skills training and agoraphobia treatment interventions were effective in enhancing positive meta-emotion and psychological resilience among adolescent girls with a history of sexual abuse during the post-test and follow-up stages (p < 0.05). However, only the agoraphobia treatment was effective in improving negative meta-emotion. There was a significant difference between the two experimental groups regarding the effectiveness of treatment on hyperemotion and psychological resilience. The treatment for agoraphobia proved to be more effective than the training in self-determination skills.Discussion and Conclusion: The findings indicate that both treatment methods—agoraphobia therapy and self-determination skills training—are effective in enhancing the psychological well-being of adolescent girls who have experienced sexual abuse. Notably, agoraphobia therapy demonstrates a greater effectiveness in improving hyper-emotionality and psychological resilience among these individuals. Consequently, these treatments can serve as complementary approaches to alleviate the psychological challenges faced by girls who have undergone sexual abuse.